Os ardis da hipermodernidade: jovens, cotidiano escolar, educação, consumo e integração social - Rafael Lopes de Sousa (EccoS – Revista Científica)
This article presents, in the context of the investigations that are taking place about the culture of closeness and distancing of young people with formal education, the prospect of a reading that seeks to understand what policy - teaching is offered to the youth of hypermodernity. Analyze landscapes in transition, and moments of ruptures that are evident in the speeches and questions that educators and learners have to fight the assumptions of humanization by consumption. The analysis stems from questioning the symbolic character or strategic merchandise plays in the existence of the young , is considering the possibility or not of Brazilian society to risk new experiences and formulations of citizenship that the agenda of democratization school brought some issues to think about crucial in contemporary Brazil . Given this perspective, I analyze the intervention practices within the school and highlight the importance of the commodity fetish has played and plays in the reorientation of the role and social status of the school for the hypermodernity.